Atopic dermatitis shows significant cutaneous comorbidity: results from large‐scale investigations in the working population. (4th September 2019) - Zander, N.; Augustin, M.; Reinert, R.; Schäfer, I.
Abstract: Background: Atopic dermatitis (AD) is one of the most common chronic inflammatory diseases of the skin. Rare large‐scale data have been published on the prevalence of concomitant dermatoses. Objective: To analyse the prevalence and cutaneous comorbidity of AD in Germany. Methods: A cross‐sectional study on voluntary whole‐body skin checks by trained dermatologists in over 400 companies throughout Germany reflecting the adult working population was conducted. Prevalence ratios (PR) were calculated to compare dermatological comorbidity in employees with and without current AD. A logistic regression analysis controlling for age, sex and skin type revealed odds ratios (OR) of the occurrence of skin diseases in AD. Results: A total of N = 118 939 people were examined between 2006 and 2017 (43.2% female, mean age 43.2 ± 10.7 years, min. age 16 years, max. age 70 years). AD (point prevalence) was identified in 1.45% (men: 1.50%, women 1.39%) and decreased significantly with age. Self‐reported lifetime prevalence of AD was 4.95% (men: 3.72%, women: 6.55%). The following skin diseases were significantly more frequent in people with current AD: Contact dermatitis (PR: 3.38), hand eczema (PR: 4.62), exsiccation dermatosis (PR: 2.19), folliculitis (PR: 1.95) and port‐wine stains (PR: 1.49). Among those, folliculitis was the most frequent (prevalence in AD 16.42%). Controlled for age, sex and skin type, AD was significantly associated with – among others – hand eczema (OR: 3.96; 95% CI: 2.95–5.32), contact dermatitis (OR: 2.97; 95% CI: 1.50–5.88) and exsiccation dermatosis (OR: 1.78; 95% CI: 1.30–2.44). Psoriasis was significantly less frequent in people with AD (OR: 0.61; 95% CI: 0.39–0.94). Conclusion: In summary, cutaneous comorbidity is frequent and of great importance in people with AD, suggesting the need for comprehensive, dermatologically guided diagnostics in AD.